Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1101/2020.12.20.20248420
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infections in people with PCD: neither frequent, nor particularly severe

Abstract: People with pre-existing chronic health conditions are reportedly at high risk of getting the coronavirus disease (COVID-19) and of having a severe disease course but little data exist on rare diseases such as Primary Ciliary Dyskinesia (PCD). We studied risk and severity of SARS-CoV-2 infections among people with PCD using data from the COVID-PCD, a participatory study that collects data in real-time directly from people with PCD. Data was collected using online questionnaires. A baseline questionnaire collec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…It has been speculated that this could be explained by the under-diagnosis of CRD in some countries in comparison to other chronic diseases, as well as by a deep commitment from patients and parents in practicing careful protective behaviors in order to avoid respiratory infections. In fact, these patients and their families are inevitably more prone to careful personal protection due to consolidated experience in hand hygiene, mask wearing, and social distancing [34][35][36]. Some authors suggest that CRD treatments may reduce the risk of infection or developing COVID-19, such as the chronic administration of azithromycin [37] and inhaled corticosteroids (ICS).…”
Section: Methodsmentioning
confidence: 99%
“…It has been speculated that this could be explained by the under-diagnosis of CRD in some countries in comparison to other chronic diseases, as well as by a deep commitment from patients and parents in practicing careful protective behaviors in order to avoid respiratory infections. In fact, these patients and their families are inevitably more prone to careful personal protection due to consolidated experience in hand hygiene, mask wearing, and social distancing [34][35][36]. Some authors suggest that CRD treatments may reduce the risk of infection or developing COVID-19, such as the chronic administration of azithromycin [37] and inhaled corticosteroids (ICS).…”
Section: Methodsmentioning
confidence: 99%
“…COVID-PCD is a participatory research project where people with PCD have an active role in all stages of research from the design of the study, its content, the piloting, and communication of results. Details about the study methods have been published [24, 25]. In short, the COVID-PCD study includes persons of any age from anywhere in the world with a confirmed or suspected diagnosis of PCD.…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 ] As of March 2021, the number of persons with COVID-19 worldwide was approximately 115 million, with more than 2.5 million deaths. [ 3 ] COVID-19 has several clinical manifestations. The main presenting symptoms are fever and respiratory symptoms, such as cough, sputum production, and shortness of breath.…”
Section: Introductionmentioning
confidence: 99%